EXPLORATION OF ETHNOMATHEMATICS RULES ON BARK PAINTING OF ASEI SOCIETY IN SENTANI AS A SOURCE OF SCHOOL MATHEMATICS LEARNING - HELEN JOHANNA DUMATUBUN (Sean Institute, 2021)
The presence of ethnomathematics as a bridge between culture and mathematics, can be utilized in the learning process of school mathematics. If teachers integrate ethnomathematics into school math learning then students are easier to understand when mathematical concepts related to ethnomathematics are taught because ethnomathematics exists in everyday people's lives. This research aims to (1) Explore and describe the ethnomathematics rules contained in the bark paintings of the Asei people in Sentani, (2) Explore and describe the geometric patterns contained in the bark paintings of the Asei community in Sentani, (3) Explore and describe which rules are contained in the bark paintings of the Asei community in Sentani that can be used as a source of school mathematics learning. The type of research used in this study is qualitative descriptive research. The object in the study was the Ethnomathematics Rule on Asei in Sentani Society's Bark Paintings. The results showed (1) There are ethnomathematics rules in the bark painting of the Asei community in Sentani, namely parallel lines, perpendicular lines, arch lines, curves, angles, folding symmetry, rotary symmetry, triangles, rectangles, trapezoids, kites, parallelogram, rhombus, circles and their elements, ellipses and transformational geometry, (2) Motifs on the bark painting of Asei people in sentani, forming geometric patterns that contain the concept of transformational geometry, namely translation, reflection, rotation and dilation, (3) Asei community bark paintings in Sentani that contain ethnomathematic rules namely parallel lines, perpendicular lines, curves, angles, folding symmetry, triangular swivel symmetry, rectangles, trapezoids, kites, parallels, splits, circles and their elements, ellipses, translation, reflection, rotation and dilation, can be used as a source of learning school mathematics